Parentifikasi dan Pola Komunikasi dalam Keluarga: Pengalaman Fenomenologis Anak Sulung - Cinta Nassapramita; Farid Rusdi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
responsibilities that should be carried out by the parents. This phenomenon is commonly experienced by firstborn children in families with unequal communication patterns, economic pressure, or emotional conflict. This study aims to understand the meaning of parentification and to describe the communication patterns between firstborn children and their parents in families experiencing role imbalance. The theoretical framework includes family systems theory, parentification theory, family communication theory, and role theory as the basis for understanding the relationships and interaction patterns that emerge within the family. This study employed a qualitative phenomenological approach through in-depth interviews with three informants who experienced parentification with varying intensities. The findings indicate that parentification appears through both emotional and instrumental roles, such as mediating conflicts and managing the family’s emotional atmosphere. The communication patterns formed tend to be one-way, provide limited space for expression, and place the child in a position of maintaining family stability. Parentification is understood ambivalently, both as a form of moral responsibility and as a source of psychological pressure and emotional fatigue. This study concludes that empathetic communication and clear generational boundaries are necessary to ensure that a child’s role remains aligned with their developmental stage. Parentifikasi merupakan kondisi ketika anak mengambil alih tanggung jawab emosional maupun instrumental yang seharusnya dijalankan oleh orang tua. Fenomena ini sering dialami anak sulung dalam keluarga dengan komunikasi yang tidak setara, tekanan ekonomi, atau konflik emosional. Penelitian ini bertujuan untuk memehami makna parentifikasi serta menggambarkan pola komunikasi antara anak sulung dan orang tua dalam keluarga yang mengalami ketidakseimbangan peran. Teori yang digunakan meliputi teori sistem keluarga, teori parentifikasi, teori komunikasi keluarga, dan teori peran sebagai dasar untuk memahami hubungan dan pola interaksi yang muncul dalam keluarga. Penelitian ini dilakukan dengan pendekatan kualitatif fenomenologis melalui wawancara mendalam terhadap tiga informan yang mengalami parentifikasi dengan intensitas berbeda. Hasil penelitian menunjukkan bahwa parentifikasi muncul melalui peran emosional dan instrumental, seperti menjadi penengah konflik, mengatur suasana keluarga. Pola komunikasi yang terbentuk cenderung bersifat satu arah, kurang memberi ruang ekspresi, dan membuat anak berperan untuk menjaga stabilitas keluarga. Parentifikasi dimaknai secara ambivalen, baik sebagai bentuk tanggung jawab moral maupun sebagai sumber tekanan psikologis dan kelelahan emosional. Penelitian ini menyimpulkan perlunya komunikasi empatik dan batas generasi yang jelas agar peran anak tetap sesuai pada tahap perkembangannya.